Toxins Are an Excellent Source of Therapeutic Agents against Cardiovascular Diseases - Koh, Cho Yeow; Modahl, Cassandra M.; Kulkarni, Namrata; Kini, R. Manjunatha (Seminars in Thrombosis and Hemostasis, 2018)
Venomous and hematophagous animals use their venom or saliva for survival, to obtain food, and for self-defense. Venom and saliva from these animals are cocktails of bioactive molecules primarily composed of proteins and peptides. These molecules are called toxins because they cause unwanted consequences on prey. They exhibit unique, diverse, and specific biological activities that perturb normal physiological processes of their prey and host. However, the potential of toxins as inspirations for the development of therapeutic agents or pharmacological tools has also long been recognized. In addition to their small size, the exquisite selectivity and structural stability of toxins make them attractive as starting molecule in the development of therapeutic and diagnostic agents. Drug discovery and development from venomous and hematophagous animals against cardiovascular diseases have been particularly successful. Some of the notable success include antihypertensive (captopril and enalapril) and antiplatelet agents (tirofiban and eptifibatide), as well as anticoagulants (lepirudin and bivalirudin). Highlighted in this review are many venom or saliva-derived cardiovascular-active proteins and peptides of therapeutic interest, including those that are currently in preclinical stages and those that have been approved by FDA and currently in the market. The authors attempt to summarize their structure, function, mechanism of action, and development with respect to cardiovascular diseases.
Keywords: Blood-feeding animals; drug discovery; antiplatelet drug; blood coagulation; fibrinolysis